Lek dynamics and range-wide morphometric patterns of lesser prairie-chickens - Hildebrant Aulicky, Carly S. (Kansas State University, 2020)
The lesser prairie-chicken (Tympanuchus pallidicinctus) is a lek-breeding prairie-grouse of the Southern Great Plains. The lesser prairie-chicken range spans four ecoregions with an east-west precipitation gradient and is subject to severe droughts on a 5-10 year cycle. The influence of the range-wide precipitation gradient and severe drought cycle on lesser prairie-chicken morphology is unknown and a range-wide morphometric compilation has never been assembled. The lesser prairie-chicken population booms and busts in response to drought and estimates of population trends are made from counts of displaying males on leks. Despite the conservation importance of leks, there are many untested assumptions about how leks form on the landscape and what factors determine their persistence into subsequent breeding seasons. My dissertation seeks to fill these knowledge gaps, by (1) assembling a range-wide synthesis of lesser prairie-chicken morphometrics data, (2) determining severe weather influences on morphometric traits, (3) test the hotspot hypothesis as an explanation for lek formation, (4) determine factors that influence lek persistence and (5) evaluate lek formation and persistence findings in translocated population that has no existing lek complex. I assembled a range-wide data set of (n = 2,048) lesser prairie-chicken morphometrics from the period of 1986 to 2019 and compared among ecoregions and weather conditions based on the Palmer Drought Severity Index. Lesser prairie-chicken morphometric traits are largest in the Short-Grass and Sand Shinnery Oak Prairies and smaller in in the Mixed-Grass and Sand Sagebrush Prairies. Morphometric changes following years of extreme weather are universal across ecoregions, where adult female traits remain unaffected and male sexually selected traits increase in size after extreme weather. Incredibly, lesser prairie-chicken body fat during spring lekking is tightly constrained by sex with males exhibiting 2-3% body fat, whereas females exhibited 4-8% across all weather conditions. I tested the hotspot hypothesis, which posits that leks should form in areas where males are most likely to encounter females, and anthropogenic and female movement data as determinants of lek persistence in the Short-Grass Prairie/CRP Mosaic and Mixed-Grass Prairie ecoregions of Kansas with 143 GSP-backpacked females from 2013-2016 and 53 individual leks. As a lek-breeding species, lesser prairie-chicken females are solely responsible for incubating their nest and raising broods, which creates a sexually driven difference in space and habitat use that is reflected in both the formation and persistence of leks on the landscape. I found that lesser prairie-chicken lek dynamics are driven by female habitat constraints, where increased female space use and number of nest sites starting at a 5 km scale (F₅,₇₈ = 2.50, P = 0.04) determines the number of males displaying at leks and concentrations of female spatial use determines where new leks form on the landscape. I then compared patterns of established lek complexes to the dynamics of lek formation and persistence in the translocation of lesser prairie-chickens (n = 411) to the Sand Sagebrush Prairie Ecoregion in 2016-2019. The formation and persistence of leks by translocated birds is also driven by female space utilization, where the location of newly formed leks comprised of translocated birds can be explained by female nesting attempts and space use and the persistence and stability of translocation leks can be explained by multiyear nesting efforts by females starting at a 5 km buffer (F₄,₂₁ = 6.57, P = 0.01). My research offers an explanation for the spatial-temporal dynamics of lek formation and persistence on the landscape and provides means to use morphometrics to evaluate weather stressors and resource allocation in lesser prairie-chickens.
Keywords: Lesser prairie-chicken; Translocation; Morphology; Lek persistence; Nutrient reserves; Hotspot hypothesis